Drugs against osteoporosis in perimenopausal and postmenopausal women - Lv, Hong; Zhang, Yaoyang; Li, Jiaqian; Jia, Qiucheng; Yu, Yi; Tang, Huimin; Chen, Wanying; Yang, Yun; Jiang, Qiong; Chen, Jiming (Frontiers in Medicine, 2025)
The prevalence of osteoporosis will continue to rise as the world’s population ages. Since women’s bones are smaller and thinner than men’s, bone loss accelerates as estrogen levels fall. Based on their primary effects, drugs used to treat osteoporosis can be categorized into three groups: 1. Anti-resorptive medications. These primarily prevent osteoclasts from resorbing bone, which has a secondary effect on bone growth. Commonly used anti-resorptive drugs include bisphosphonates, denosumab, hormone replacement therapy, and raloxifene. 2. Anabolic medicines. These mainly stimulate osteoblasts to produce new bone, although they may also affect bone resorption. Common examples include teriparatide, romosozumab, and parathyroid hormone. 3. Phytoestrogens. These are non-steroidal, naturally occurring plant compounds with estrogenic and/or anti-estrogenic properties that resemble estrogen.